The crisis in figures - Antonini, Ernesto; Primiceri, Giuseppe (TECHNE - Journal of Technology for Architecture and Environment, 2011)
Economic data on construction market performance culled from recently published analysis and studies, have served to highlight and quantify the phenomena that have driven the negative global economic downturn, affecting the construction sector in particular, over the last two years, with obvious repercussions also for Italy. Although there were a few rallying signs that the downward trend was easing off slightly in early 2011 – both in Europe and, albeit rather more hesitantly, in Italy – those tenuous hopes for recovery were not backed up by actual statistical indicators, potentially providing some indication of promising development trends. Of the few emerging dynamics in the American market, which is recovering more swiftly than in Europe, there seems to have been a marked increase in the production of sustainable or “green” buildings, which are taking over increasingly larger slices of the market.